Punishment for the Crimes against Person According the Criminal Code of Poland - Batuevich Mulyukov, Farkhad; Viktorovna Danilova, Valentina (International Journal of Criminology and Sociology, 2022)
This study examines the types of sanctions for crimes against the person provided for by Special part of the Criminal code of Poland (hereinafter referred to as the Criminal code). The system is analyzed and in more detail-certain types of criminal attacks on the person in comparison with the analogous norms of the criminal code of the Russian Federation and the criminal legislation of some other States. The introduction substantiates the relevance of the research, defines the object and purpose of the research. Based on the research, a number of conclusions and recommendations for changing section VII of the Special part of the criminal code of the Russian Federation are formulated. Asked to borrow a positive experience of the Polish legislator to change the order of sections in a Special part of the Criminal code of the Russian Federation, justifies measures to prevent attacks on the person in connection with the pandemic coronavirus in addition the criminal code of Poland and the criminal code – establish liability for evading treatment of a difficult-to-treat infectious disease that is dangerous to others, as well as adopt a Law on the prevention of infection with a difficult-to-treat infectious disease, in which it would be possible to establish compulsory hospitalization, based on a court decision, to appropriate medical institutions for patients with these diseases who evade examination or treatment.